Diatom oxygen isotopes: evidence of a species effect in the sediment record - Swann, George E.A.; Leng, Melanie J.; Sloane, Hilary J.; Maslin, Mark A.; Onodera, Jonaotaro (AGU and the Geochemical Society, 2007)
Diatom oxygen isotope measurements are commonly made on bulk mixed species assemblages due to the difficulty in purifying and separating individual taxa. As such, it is essential to understand processes in diatoms which may lead to isotope offsets both between and within individual species. Existing studies have suggested that mechanisms which may lead to isotopes offset in diatoms, such as vital effects, are either nonexistent or negligible. Here, we present a suite of diatom oxygen isotope data from the onset of major Northern Hemisphere Glaciation at ODP site 882 in the northwest Pacific Ocean which display large offsets (mean = 1.23%, max = 3.51%, error = 0.84%) between two different size fractions (75–150 um and >150 um) that are dominated by only two species: Coscinodiscus marginatus and Coscinodiscus radiatus. These offsets are most likely size related, although additional interspecies and intraspecies effects may also be important in determining the exact magnitude of the offsets. Consequently, considerable care is needed when interpreting bulk diatom oxygen isotope data in relation to paleoenvironmental change, especially when the amount of stratigraphical change within the isotopes is small.